2004
DOI: 10.1007/bf02350992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow disturbances remaining at the beginning of diastole on intraventricular diastolic flow and colour M-mode Doppler echocardiograms

Abstract: A computational model of the fluid dynamics of intraventricular flow was used to investigate the importance of the effects of flow disturbances existing within the left ventricle (LV) at the onset of diastole on a diastolic flow field. The simulation started with a quiescent flow state; it continued for a number of cardiac cycles to obtain a cyclically repeatable flow. After the flow became periodic, the initial diastolic flow was not quiescent: flow disturbances, remnants of a systolic flow, were present with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The ventricle shape was simplified by using the method proposed by Nakamura et al. (10,11). The configuration of the LV model is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ventricle shape was simplified by using the method proposed by Nakamura et al. (10,11). The configuration of the LV model is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The computational model of the LV was constructed using computer-aided design software (Pro/ ENGINEER, PTC Japan,Tokyo, Japan).The shape of the ventricular cavity was assumed to be a bended tube having a continuously changing cross section. The ventricle shape was simplified by using the method proposed by Nakamura et al (10,11). The configuration of the LV model is shown in Fig.…”
Section: Modelmentioning
confidence: 99%
“…It is worth mentioning that the mitral vortex is stretched during systolic contraction and is ejected and disappears almost completely before the onset of diastolic filling. Therefore, the remaining vorticity from the previous cycle weakly affects the mitral inflow vortex and the diastolic flow can be considered vortexfree before the beginning of ventricular filling [72,135]. …”
Section: P = 0004mentioning
confidence: 99%
“…They discussed the relationship between the growth of an intraventricular vortex and a Doppler-derived clinical index for left ventricular diastolic function, the so-called "flow propagation velocity," and provided the fluid mechanical basis of this index. Their subsequent analysis of the utility and limitations of this index showed that the flow propagation velocity was not sensitive to flow disturbances remaining from systole (93) and to ventricular untwisting (94) . Nakamura et al also addressed the importance of the opening mode of the mitral valve orifice on vortex formation within the left ventricle during diastole (95) and showed that the vortex structure affected left ventricular flow ejection into the aorta (96) .…”
Section: Computational Analysis Of the Intracardiac And Aortic Flowsmentioning
confidence: 99%